Surface Membrane Glycopeptides Which Coincide with Virus Transformation and Tumorigenesis - Glick, Mary Catherine (1974)
Glycopeptides from the surface of clones of hamster embryo cells were examined at various intervals after infection with polyoma virus. Two types of transformed cells were examined: (i) clones that showed delayed transformation or an initially low tumorigenicity, and (ii) clones that were rapidly transformed showing an initially high tumorigenicity. The glycopeptides were removed from the cell surface by trypsin and, after Pronase digestion, were examined by filtration through Sephadex G-50. With delayed transformation, a specific group of glycopeptides was increasingly evident over an 85-day period as the cells showed phenotypic properties of transformation and the ability to form tumors. In the other series, all but one clone of hamster embryo cells showed rapid transformation after infection with polyoma virus. This clone was less tumorigenic and showed little of the specific glycopeptides. In all cases of delayed or rapid transformation examined, the specific group of glycopeptides increased proportionately to the ability of the cells to form tumors. All of the cells derived from progressively growing tumors formed by injection of these transformed hamster cells into adult animals showed an abundance of this group of glycopeptides. These results suggest that specific surface membrane glycopeptides accompany viral transformation and tumorigenesis.